Nothing happened, something happened: Silence in a makerspace. Issue 2 (April 2019) - de Vaujany, François-Xavier; Aroles, Jeremy
An ever-increasing range of work activities occur in open spaces that require collective discipline, with silence emerging as a key feature of such workplace configurations. Drawing from an ethnographic examination of a makerspace in Paris, we explore the ways in which silence is incorporated into new work practices in the context of their actualization, embodiment and apprenticeship. Through its engagement with the conceptual work of Merleau-Ponty, this article does not posit silence as the opposite of sounds or as a passive achievement. Silence is inscribed in a learning process and requires numerous efforts to be maintained (e.g. body postures to avoid staring into the eyes of someone entering into an open space, wearing headphones, etc.). It is also the envelope of numerous noisy acts that take place in the phenomenological body and in the embodied practices of workers. We argue that 'silencing' is an event ordering that gives direction to what 'happens' in collective work activities and is central to the process of embodied learning in collaborative spaces.